CuAAC in a Distal Pocket: Metal Active‐Template Synthesis of Strapped‐Porphyrin [2]Rotaxanes. Issue 55 (11th July 2017) - Miyazaki, Yuta; Kahlfuss, Christophe; Ogawa, Ayumu; Matsumoto, Takashi; Wytko, Jennifer A.; Oohora, Koji; Hayashi, Takashi; Weiss, Jean
Abstract: The synthesis of a porphyrin rotaxane by dipolar cycloaddition takes advantage of the ditopic character of a phenanthroline‐strapped porphyrin. The success of the click reaction was conditioned by the presence of both a coordinatively unsaturated metal in the porphyrin and a copper(I) bound to the phenanthroline, pointing at a new "tandem active metal template" mechanism. Abstract : All strapped in : Two metals cooperate for a click reaction leading to new [2]rotaxanes derived from a ditopic phenanthroline‐strapped porphyrin. In addition to the copper active‐template effect, coordination of the azide to the porphyrin's metal core is necessary to generate sterically constrained [2]rotaxanes.